Profiling the Mental Health Needs of a Youth Population With View to Informing Programme Planning in a Local Community-Based Youth Cafe - O'Donoghue, Brid (Trinity College Dublin. School of Psychology, 2007)
The aim of this study was to develop a mental health profile on the population of young people in Elphin, Co. Roscommon. It also looked at the specific types of coping strategies and the relationship of those coping strategies to various levels of mental health. A focus group of six students was also carried out to gather recommendations for the organisation and running of the youth cafe. The participants involved were 112 students from each school year in Elphin Community College, with an age range of 12-18, with a mean age of 14.6 (SD = 1.86), unbalanced for gender. Each participant completed a set of questionnaires comprised of the Strengths and Difficulties Questionnaire, the 12 item General Health Questionnaire, the Coping Inventory for Stressful Situation, the 21 item Depression Anxiety Stress Scales, and the Youth Self Report. Results found 10.7% of students presented with very good mental health, 72.3% had normal levels and 17% were found to have poor mental health. All three hypotheses were supported. It was found that individuals who employ avoidance-based coping strategies are more likely to have better levels of general mental health. Students who employ emotion-based coping strategies internalise more and are more likely to have poorer general mental health, and also a variety of other problems, such as conduct, somatic and social problems. Future research directions in this area include choosing a period of testing in the school calendar when the students are settled in their school routine and there are no visible signs of disruption.
Keywords: Mental health; Community health; Roscommon; Youth psychology